1992
DOI: 10.1002/j.1556-6676.1992.tb02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Esteem Groups: A Synthesis of Consciousness‐Raising and Assertiveness Training

Abstract: This article reviews the history of consciousness-raising groups and assertiveness training, discusses the strengths and limitations of each, and proposes that the features of these two models of change can be combined in self-esteem enhancement groups. The components and interventions associated with self-esteem groups are outlined for counselors who wish to conduct self-esteem enhancement experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Feminist theory (Jordan et al, 1991) postulates that women's groups may reduce social isolation by offering participants an opportunity to share common life experiences in order to connect with one another (Burden & Gottlieb, 1987;McManus, Redford, & Hughes, 1997) and address topics difficult to discuss in mixed gender groups (Enns, 1992). In the context of disability, greater self esteem has been associated with better integration in social networks (Crisp, 1996).…”
Section: Social Connectednessmentioning
confidence: 99%
“…Feminist theory (Jordan et al, 1991) postulates that women's groups may reduce social isolation by offering participants an opportunity to share common life experiences in order to connect with one another (Burden & Gottlieb, 1987;McManus, Redford, & Hughes, 1997) and address topics difficult to discuss in mixed gender groups (Enns, 1992). In the context of disability, greater self esteem has been associated with better integration in social networks (Crisp, 1996).…”
Section: Social Connectednessmentioning
confidence: 99%
“…This finding is parallel to McGirr and Sullivan's research (2017) which showed that raising consciousness about domestic violence and its roots in patriarchy increased women's sense of confidence in themselves and in their ability to cope with challenging experiences. Similarly, feminist practitioners have long advocated for an examination of relational issues in the context of social and structural inequalities (Enns, 1992a, 1992b, 1993; Evans, Kincade, Marbley, & Seem, 2005; Israeli & Santor, 2000). In light of the present evidence, one suggestion for future preventive efforts is to foster a contextualized definition of dating violence, exposing its social and patriarchal origins.…”
Section: Discussionmentioning
confidence: 99%
“…Assertiveness training has been found to be particularly effective because it gives women the voice to speak their needs . Several researchers have recognized the value of assertiveness training for women (Enns, 1992;McBride, 1997), especially for those women who feel intimidated about speaking out .…”
Section: Challenges For the Populationmentioning
confidence: 99%
“…Also, the active identification of people, places, and thoughts that support, comfort, and energize the members would promote involvement and discussion about areas that need to be improved (McManus, Redford, & Hughes, 1997) . Some literature notes the importance of a combination of factors to assist women in dealing with stress including support groups, assertiveness training, and learning how to say no (Enns, 1992;Rayburn, 1986) .…”
Section: Employment Counseling Interventions and Techniquesmentioning
confidence: 99%